ACADEMY AND EDUCATION IN GANDHIAN PERSPECTIVE: EXPLORING THE EMPIRICAL ASSESSMENT - Ms. A.N. Singh (JETA (Journal of English Teaching and Applied Linguistic), 2023)
Mahatma Gandhi was the practical follower of peace. Gandhi always maintained that education must be for the attainment of the moral and spiritual development of the character. According to Gandhi, cultural and moral side of learning best suits the personality of the citizens. For him, ultimate goal of education is to spark a pursuit of knowledge in the child from the beginning of his learning process and it will definitely lead towards innovative mindset. Gandhi stressed on the development of a child as a whole, not just the mind. He advocates the all-round education tendency. For a civilized and cultured society, education is the only way. This study tries to catch out the Gandhian perspectives and his believes on education system and will also find out that how his principles were as fresh as were then and still realizes the importance of his educational ethics. ‘Knowledge is power’ will always be acknowledged. A saying truly said, ‘‘Gandhi is dead but Gandhism is alive”.